2012
DOI: 10.5216/rpt.v41i4.21708
|View full text |Cite
|
Sign up to set email alerts
|

DETECÇÃO DE BETALACTAMASES DE ESPECTRO ESTENDIDO (ESBL) EM ISOLADOS DE Escherichia coli UROPATOGÊNICAS (UPECs) ORIUNDOS DE PACIENTES DA COMUNIDADE

Abstract: A produção de betalactamases de espectro estendido (ESBL) consiste em um importante mecanismo de resistência aos antimicrobianos betalactâmicos. O vasto uso desses antibióticos no tratamento das infecções do trato urinário (ITU) tem agravado ainda mais esta problemática. As bactérias do tipo UPEC são consideradas as principais responsáveis por este tipo de infecção. Estudos para a compreensão da diversidade dessas enzimas no Brasil são escassos e, além disso, muitos deles são direcionados à pesquisa de isolado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(25 reference statements)
1
2
0
1
Order By: Relevance
“…Of all the samples analyzed here, 95% presented genes encoding ESBL. Carmo et al,39 in agreement to our results, found the prevalent gene was bla TEM and in sequence, the gene bla CTX-M . The bla SHV gene is involved with plasmid transmission, where this facility in gene transmission is possibly directly involved with the highest percentage found in hospital isolates, since this environment is very susceptible to the most diverse types of microorganisms and genetic recombination among them 39…”
Section: Discussionsupporting
confidence: 93%
“…Of all the samples analyzed here, 95% presented genes encoding ESBL. Carmo et al,39 in agreement to our results, found the prevalent gene was bla TEM and in sequence, the gene bla CTX-M . The bla SHV gene is involved with plasmid transmission, where this facility in gene transmission is possibly directly involved with the highest percentage found in hospital isolates, since this environment is very susceptible to the most diverse types of microorganisms and genetic recombination among them 39…”
Section: Discussionsupporting
confidence: 93%
“…Com isso, faz-se necessário que mais pesquisas sejam desenvolvidas fora do ambiente hospitalar, para que novas formas de tratamento possam ser desenvolvidas a fim de tratar efetivamente infecções por bactérias com sensibilidade diminuída aos tratamentos convencionais 13,21 . Há relatos que indicam claramente que a resistência aos antibióticos contra a E. coli causadoras de ITU comunitária vem obtendo um crescimento significativo 18,22 . Portanto, monitorar o comportamento frente aos antimicrobianos e conhecer o padrão de resistência dos microrganismos causadores de ITU, a fim de que o tratamento, mesmo que empírico, possa resultar na sua eliminação, é muito importante 14 .…”
Section: Introductionunclassified
“…Among the several mechanisms of resistance to antibiotics, one of the most important is the production of enzymes that have the property of inactivating antimicrobials (CARMO et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…If concentrations of these strains are high, the hospital effluents, municipal sewage, and sewage treatment plants can become reservoirs for the selection of resistant bacteria. The monitoring of this occurrence contributes substantially to delineate the magnitude of the problem and to suggest appropriate containment measures (CARMO et al, 2012;PRADO et al, 2008;SILVA;LINCOPAN, 2012).…”
Section: Introductionmentioning
confidence: 99%